The Effect of Religiosity, Perception, Income, and Media Access to Information on Public Waqf Intentions in Cash Waqf Linked Sukuk in City of Surabaya - Triya Oftafiana; Siswahyudianto - (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2023)
Indonesia as a country that has the largest Muslim population in the world makes it a very large waqf potential. However, the development of productive waqf is still not massive, one of which is Cash Waqf Linked Sukuk. This is due to a lack of religious knowledge, access to information media, or studies on productive waqf and public awareness for waqf. In addition, the domination of public perceptions of traditional waqf is also an obstacle in the development of CWLS instruments. Therefore, this study aims to determine the effect of religiosity, perception, income, and access to information media on the intention of waqf people in Cash Waqf Linked Sukuk in the City of Surabaya. This research method uses a quantitative approach with primary data in the form of questionnaires distributed to 168 respondents who meet the criteria. The sampling technique used is probability sampling by determining individual samples by accidental sampling. The data analysis technique in this study used multiple linear regression analysis. Based on the regression test, it shows that the variables of religiosity, perception, and income have a positive and significant effect on the intention to waqf in CWLS. While the information media access variable has no positive and significant effect on waqf intentions in CWLS. Based on the f test, it shows that the five independent variables jointly affect the dependent variable with f count > f table (40.176 > 2.43) with a significance value (0.000 <0.05). The coefficient of determination test shows that 49.6% of the independent variables can influence the dependent variable, while the rest are influenced by other variables.